2020
DOI: 10.3390/ijms21082963
|View full text |Cite
|
Sign up to set email alerts
|

Probing Hexaminolevulinate Mediated PpIX Fluorescence in Cancer Cell Suspensions in the Presence of Chemical Adjuvants

Abstract: Exogenous administration of hexaminolevulinate (HAL) induces fluorescent protoporphyrin IX (PpIX) accumulation preferentially in cancer cells. However, the PpIX fluorescence intensities between noncancer and cancer cells are highly variable. The contrast between cancer and noncancer cells may be insufficient to reliably discriminate, especially at the single cell level in cancer diagnostics. This study examines the use of the chemical adjuvants dimethylsulphoxide (DMSO) or deferoxamine (DFO) to enhance the HAL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Various inhibitors of these chelating and efflux steps of the metabolism have been shown to be effective in increasing PpIX accumulation in some cancer types [15], although results for bladder cancer have not been reported. Results from our previous works indicated that the cell microenvironment plays an important role in the regulation of PpIX accumulation when suspended bladder cells are treated with HAL [16]. In this study, we hypothesize that reducing the PpIX efflux and FECH activity with inhibitors and iron chelators could enhance HAL-induced PpIX fluorescence within bladder cancer cells (Figure 1).…”
Section: Introductionmentioning
confidence: 56%
See 2 more Smart Citations
“…Various inhibitors of these chelating and efflux steps of the metabolism have been shown to be effective in increasing PpIX accumulation in some cancer types [15], although results for bladder cancer have not been reported. Results from our previous works indicated that the cell microenvironment plays an important role in the regulation of PpIX accumulation when suspended bladder cells are treated with HAL [16]. In this study, we hypothesize that reducing the PpIX efflux and FECH activity with inhibitors and iron chelators could enhance HAL-induced PpIX fluorescence within bladder cancer cells (Figure 1).…”
Section: Introductionmentioning
confidence: 56%
“…The cells were then treated with the inhibitors under investigation (EDTA, selumetinib, U0126, genistein, SA, deferiprone and trametinib), for a different amount of time and at different temperatures, as summarized in Table 2 . The effect of the seven PpIX conversion and/or membrane transport inhibitors on the overall HAL-induced fluorescence of the cells was then quantified following established fluorescence microscopy procedures [ 16 , 23 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To address this, many prodrugs of ALA have been studied to offset the hydrophilic nature of ALA itself, enhance stability at physiological pH, and to improve targeting of cancerous cells [17,18]. The formation of lipophilic esters as in the clinically approved methyl ester (Metvix) and hexyl ester (Hexvix), has been shown to be highly effective for the enhancement of ALA uptake, but the use of simple ALA-esters presents a challenge with respect to specificity, causing a nonspecific distribution of ALA in all cell types post administration of the prodrugs [19].…”
Section: Introductionmentioning
confidence: 99%
“…The device couples EpCAM-based immunoaffinity with photodynamic principles established in clinical urology , to specifically identify malignant cells of epithelial origin shed in urine samples. Our approach has achieved promising results with model cell lines from both bladder and prostate cancer origin. , However, results in patients samples were challenged by a number of false-positive results . As the cells lining the urinary tract (squamous, renal tubular, and transitional cells) are both epithelial and adherent in nature, a careful examination of the conditions in which the specificity of the immune-capture toward urogenital cancer cells can be enhanced is critical for future clinical use.…”
Section: Introductionmentioning
confidence: 99%